2020
DOI: 10.1097/gme.0000000000001568
|View full text |Cite
|
Sign up to set email alerts
|

Baseline estrogen levels in postmenopausal women participating in the MAP.3 breast cancer chemoprevention trial

Abstract: Objective: The aim of the study was to quantify baseline estradiol (E2) and estrone (E1) concentrations according to selected patient characteristics in a substudy nested within the MAP.3 chemoprevention trial. Methods: E2 and E1 levels were measured in 4,068 postmenopausal women using liquid chromatography-tandem mass spectrometry. Distributions were described by age, years since menopause, race, body mass index (BMI), smoking status, and use and durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
14
2
Order By: Relevance
“…Estrogen levels in females are lower after menopause ( Figure 2 ) [ 134 ]. In general, menopause, and the subsequent reduction in estrogen, is associated with an increase in inflammation and the development of chronic conditions in a variety of organ systems [ 135 , 136 , 137 ].…”
Section: Changes In Estrogen Levels and Impacts On The Immune Systemmentioning
confidence: 99%
“…Estrogen levels in females are lower after menopause ( Figure 2 ) [ 134 ]. In general, menopause, and the subsequent reduction in estrogen, is associated with an increase in inflammation and the development of chronic conditions in a variety of organ systems [ 135 , 136 , 137 ].…”
Section: Changes In Estrogen Levels and Impacts On The Immune Systemmentioning
confidence: 99%
“…However, in premenopausal women, estradiol levels vary during the menstrual cycle, limiting our ability to estimate the genetic effects on estradiol in females. In postmenopausal women, on the other hand, estradiol levels drop rapidly, and it has previously been suggested that the estradiol levels in females are more likely to be determined by the number of years since menopause ( 42 ). For those reasons, we performed sensitivity analyses, stratifying females by menopausal status and adjusting for age at menopause in the postmenopausal strata.…”
Section: Discussionmentioning
confidence: 99%
“…However, in premenopausal women, estradiol levels vary during the menstrual cycle, limiting our ability to estimate the genetic effects on estradiol in females. In postmenopausal women, on the other hand, estradiol levels drop rapidly, and it has previously been suggested that the estradiol levels in females are more likely to be determined by the number of years since menopause 39 . For those reasons, we performed sensitivity analyses, stratifying females by menopausal status, and also adjusting for age at menopause in the postmenopausal strata.…”
Section: Discussionmentioning
confidence: 99%